The emergence of environmental accounting / Salwana Selamat and Nazirah Naiimi - Selamat, Salwana; Naiimi, Nazirah (Fakulti Perakaunan, 2023)
Environmental accounting is a crucial field that has gained increasing prominence in recent years as societies and businesses recognize the pressing need for sustainable and responsible practices. The worldwide awareness of environmental concerns has significantly increased over the last twenty years which the obvious concerns such as climate change, the exhaustion of restricted resources, and the destruction of natural habitats. lnadequate environmental practices can significantly bring harm to both the business and its financial interests as well as the society. This article will explore on the definition, goals and challenges that associated with environmental accounting.